Arbitragem em investimento estrangeiro e o ICSID - Hernandes Neto, Antonio Marcos (2011)
The globalization changed substantially the relationships among States, breaking boundaries that were rigids until then. In this new moment in time, an opportunity also came up, by need, of expansion of the private investments towards new territories beyond the ones of their own. So, in time, the economy watched an intense transformation, by which capital gained mobility so far unknown, in a way that investments made in a given State had sources from various other States and, most importantly, coming from the reserves of the private initiative. To the private initiative guarantees started to be needed in order to that its investment did not suffer intervention from the State receiving the investment, and so that its asset wouldn't be damaged. Of these guarantees, the highlights are the investment agreements, the domestic legislation of the host State that aimed to protect the foreign investment and, at last, the international treaties. Each one of these instruments, at its own way, tried to offer security to the foreign investor, so that it would then venture in that territory. One of the main forms of guaranteeing the foreign investment is to transfer the competence to judge eventual disputes concerning such investments from the courts of the host State to international arbitration. Because it is an independent tribunal and, theoretically, better provided with resources to deal with the issue involved in such a controversy, arbitration has become attractive to investors afraid of the expropriatory acts that could be taken by the host States of their capital. The emergence of ICSID (or CIRDI) through the Washington Convention of 1965 as an institution specialized in this kind of dispute of foreign investment between private investor and host State granted even more soundness to this system. However, the ICSID jurisdiction is not simple, because it demands the analysis of various factors to its definition, both as the parties involved (ratione personae) and the subject in dispute (ratione materiae). The Washington Convention still sets forth a specific procedure to be followed by the arbitration under its auspices, as well as to the enforcement of the award stemming from it. Therefore, this is a subject filled with nuances that must be carefully analyzed and detailed